2020
DOI: 10.1002/cssc.202001633
|View full text |Cite
|
Sign up to set email alerts
|

Butane Dry Reforming Catalyzed by Cobalt Oxide Supported on Ti2AlC MAX Phase

Abstract: MAX (M n + 1 AX n) phases are layered carbides or nitrides with a high thermal and mechanical bulk stability. Recently, it was shown that their surface structure can be modified to form a thin non-stoichiometric oxide layer, which can catalyze the oxidative dehydrogenation of butane. Here, the use of a Ti 2 AlC MAX phase as a support for cobalt oxide was explored for the dry reforming of butane with CO 2 , comparing this new catalyst to more traditional materials. The catalyst was active and selective to synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…A Thermo Scientific Surfer instrument was used to carry out N 2 adsorption–desorption analyses at 77 K. The samples were pretreated under vacuum at 200 °C for 6 h. Surface areas were determined with the Brunauer–Emmett–Teller (BET) method, and the mesoporosity was analyzed using the Barrett, Joyner, and Halenda (BJH) method. Hydrogen temperature-programmed reduction (H 2 -TPR) profiles were obtained using a TPDRO Series 1100 from Thermo Scientific, following the procedure previously reported by Ronda-Lloret et al 6 High-resolution transmission electron microscopy (HRTEM) micrographs and transmission electron microscopy coupled with energy-dispersive X-ray spectroscopy (STEM–EDS) images were obtained on a JEOL-JEM 2100F microscope running at 200 kV. X-ray photoelectron spectroscopy (XPS) analyses were performed with a SPECS PHOIBOS 100 MCD5 hemispherical electron analyzer operating in a constant pass energy.…”
Section: Methodsmentioning
confidence: 99%
“…A Thermo Scientific Surfer instrument was used to carry out N 2 adsorption–desorption analyses at 77 K. The samples were pretreated under vacuum at 200 °C for 6 h. Surface areas were determined with the Brunauer–Emmett–Teller (BET) method, and the mesoporosity was analyzed using the Barrett, Joyner, and Halenda (BJH) method. Hydrogen temperature-programmed reduction (H 2 -TPR) profiles were obtained using a TPDRO Series 1100 from Thermo Scientific, following the procedure previously reported by Ronda-Lloret et al 6 High-resolution transmission electron microscopy (HRTEM) micrographs and transmission electron microscopy coupled with energy-dispersive X-ray spectroscopy (STEM–EDS) images were obtained on a JEOL-JEM 2100F microscope running at 200 kV. X-ray photoelectron spectroscopy (XPS) analyses were performed with a SPECS PHOIBOS 100 MCD5 hemispherical electron analyzer operating in a constant pass energy.…”
Section: Methodsmentioning
confidence: 99%
“…Before the analysis, the samples were pretreated under a helium gas flow of 80 mL·min –1 at 350 °C for 3 h and then reduced at 500 °C for 6 h under pure hydrogen. More details on the analysis procedure can be found in Ronda-Lloret et al ( 36 )…”
Section: Methodsmentioning
confidence: 99%
“… 35 We also showed that MAX phases are promising supports for CO 2 conversion reactions. 36 The thermal stability and acid–base properties of the Ti 2 AlC MAX phase increased the stability and coking resistance of a Co 3 O 4 /Ti 2 AlC catalyst during dry reforming of butane. 36 Elsewhere, Trandafir et al recently showed the potential of Pd/Ti 3 SiC 2 as a chemoselective catalyst in the hydrogenation of functionalized nitro derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…They are prepared by delaminating MAX phases, which are atomically layered solids where M is an early transition metal, A is a group IIIA/IVA element, and X is carbon or nitrogen [1]. MXenes are denoted by M n+1 X n T x , where T stands for a terminating functional group that depends on the delamination conditions [2][3][4][5]. These materials are very versatile.…”
Section: Introductionmentioning
confidence: 99%